Intrathecal Pump Implantation in the Cisterna Magna for Treating Intractable Cancer Pain - Yaling Lou; Yuefeng Rao; Zhiying Feng (Case Reports in Anesthesiology)
A 54-year-old male patient with postoperative axillary lymph node, intrapulmonary, intracranial, and cervical spine metastases of left liver cancer was suffering from severe, persistent, and pricking pain in the right dorsal shoulder and right arm since 3 months. The drug dose of the fentanyl transdermal patch was gradually increased after admission and an adjuvant analgesic was also included, but neither treatment alleviated the pain. It was gradually alleviated after intramedullary analgesic infusion through intrathecal pump implantation in cistern magna. Terminally ill patients often have the desire to spend their remaining time at home, which however becomes a challenge in the face of refractory pain. At present, no palliative chemoradiation or ablative or stimulant neurosurgical options are available to manage pain in cancer patients. Based on the findings of this report, we concluded that an intramedullary drug infusion system can have a significant analgesic effect in patients with cervical metastasis and refractory cancer pain.